Observation of Aqua-Bio fertilizer nutrients influence of Trigonella foenum- graecum L. growth in mediated Aquaponics system for food security. - D, Manjula; S, Raja (International Journal of Scientific Research in Biological Sciences, 2019)
The conception of Aquaponics is a synergistic combination of aquaculture and hydroponics that nurture plants with aquaculture water. It is the internationally improved agricultural practices, are needed to assuage rural poverty and enhance food security. Aquaponics is a soil-less combined approach to proficient and sustainable intensiﬁcation of agriculture that meets the needs of water scarcity inventiveness and generated modern farming practices in agriculture. The nutrient-rich fish water from the fish tanks is used to fertigate hydroponic production beds. To improve the production efficiency can be used bio fertilizers (Aquaponic water and Gracilaria corticata extract) as a liquid it contains organic macro, micronutrient and growth hormones. Tilapia fish produced the nutrient that is utilized by the plant Trigonella foenum- graecum L. The Physico-chemical parameter of both bio fertilizers should be assessed by using the standard procedures. The fish effluent water is compared with the Gracilaria corticata red seaweed extract by foliar spray and combining with both liquid bio fertilizers (Aquaponic water and seaweed extracts). Morphological growths of the plants were assessed. The combination of Aquaponic water and Gracilaria corticata seaweed extract was given the good result, but the estimation (15.26± 0.29, 24.06± 0.27, 30± 0.64, 35.94 ±0.28 cm plant height at 7, 14, 21 and 28 DAS) (2.6± 0.1 branches at 30, DAS) (533.67 ±11and 51 ± 1 mg shoot and root fresh weight per plant) leaf area (46.62±0.89cm2) at 28 DAS was related to the Aquaponic water in the plant Trigonella foenum- graecum L. Thus, the present result revealed that the integrated aquaponic system is the new agricultural farming systems with liquid bio fertilizers are eco- friendly practice for food security.